Fatores associados à prática de atividade física global e de lazer em idosos: Inquérito de Saúde no Estado de São Paulo (ISA-SP), Brasil - Zaitune, Maria Paula do Amaral; Barros, Marilisa Berti de Azevedo; César, Chester Luiz Galvão; Carandina, Luana [UNESP]; Goldbaum, Moisés; Alves, Maria Cecilia Goi Porto (Escola Nacional de Saúde Pública Sergio Arouca, Fundação Oswaldo Cruz, 2010)
O propósito deste estudo foi medir a prevalência e os fatores associados à prática de atividade física global e de lazer em idosos (60 anos e mais). Estudo transversal de base populacional, com amostragem em múltiplos estágios que envolveu 1.950 idosos, residentes em áreas do Estado de São Paulo. A prevalência de atividade física global (avaliada pela versão curta do Questionário Internacional de Atividade Física - QIAF) foi de 73,9% e no lazer de 28,4%. Os resultados apontam para diferenças entre os fatores associados à atividade física global e no lazer. Os segmentos sociais mais vulneráveis ao sedentarismo global e, em especial ao sedentarismo no contexto de lazer, devem ser os alvos preferenciais das políticas de saúde que buscam a promoção de estilos de vida mais saudáveis.

The purpose of this study was to measure the prevalence of global and leisure-time physical activity and associated factors in the elderly. This was a population-based cross-sectional study covering a multiple-stage sample of 1,950 subjects 60 years or older living in areas of São Paulo State, Brazil. Prevalence of global physical activity (assessed through the short version of the International Physical Activity Questionnaire - IPAQ) was 73.9%, and prevalence of leisure-time physical activity was 28.4%. The results highlight the differences between factors associated with global and leisure-time physical activities. The social groups most prone to overall sedentary lifestyle and especially to lack of leisure-time physical activity should be the main targets of health policies aimed at promoting healthier lifestyles.
Factors associated with global and leisure-time physical activity in the elderly: a health survey in São Paulo (ISA-SP), Brazil
Keywords: Atividade Motora; Atividades de Lazer; Saúde do Idoso; Motor Activity; Leisure Activities; Health of the Elderly